Freight forwarder's intermediary role in multimodal transport chains : a social network approach - Schramm, Hans-Joachim (Contributions to management science, 2012)
In this book, the business of international freight forwarding is examined from both a theoretical and empirical point of view with a special emphasis on multimodal transport chains, including sea or air transport operations. In such contexts, the freight forwarder is always considered "The Architect of Transport", but this intermediary role seems to be largely neglected in research to date. Therefore, relevant concepts from economic theory and economic sociology are employed to produce both an intermediary and a network perspective of freight forwarding in order to provide a better